PENGARUH KUALITAS PELAYANAN, PROMOSI DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN STUDI KASUS: HOTEL DI PANGKALPINANG - Deri Kusmadeni (LPPM STIE PERTIBA Pangkalpinang, 2021)
Service quality is an evaluation of the customer's long-term observation of the delivery of a company's services, while the price is one of the determining factors in brand selection related to consumer buying decisions, while the location of service facilities is one of the crucial factors that influence the success of service because the location is closely related. In relation to the potential market for service providers, a person's feelings of pleasure or disappointment that arise after comparing the performance (outcome) of the product that is thought to be against the expected performance. This study aims to determine the simultaneous effect of service quality, promotion, and brand image on customer satisfaction, the partial effect of service quality, promotion, and brand image on customer satisfaction. The test results show that the variables of service quality, promotion, and brand image have an effect on customer satisfaction.